Jovens da Educação de Jovens e Adultos na cultura digital: conexões com letramentos, sociabilidades e aprendizagens - Andrade, Jerusa Pereira de (2020)
In this thesis, the purpose is to verify, close to young people of the Youth and Adult Education (EJA), the literacy, sociability and learning processes that emerge from the use of mobile devices connected to the internet, in the context of a society marked by social differences. Although the young people of the EJA belonging to the lower classes participate, in a limited way, in the consumer society, by appropriating the cell phone such as smartphone, they are not different from other young people better socially situated, thus demonstrating, in this context, willingness and potential to interact with different groups in the reception, production and reproduction of information, communications, knowledge and languages. The study hypothesis is that young people in this research use mobile devices to interact and expand their communication networks with the world, with the school having the role of enabling access to formal and critical knowledge. The evidences were captured in the researcher's approach to the school, inspired by qualitative research and the ethnographic approach, through observation, listening, dialogue and focus group interview with high school youth of the EJA modality. Digital technologies are seen on the one hand, from the perspective of theories that bet on the benefits of authorship and on the democratization of knowledge and, on the other hand, from the perspective of theories that believe in advantages and disadvantages on risks and uncertainties. In order to support the discussions on the findings, we sought to dialogue with the theoretical contributions of Bauman (2008), Buckingham (2010), Charlot (2000, 2001), Freire (1987, 2015), Kleiman (1995, 2010, 2016), Lévy (1998), Simmel (1983), among others. The hypothesis is confirmed by the reports of the young people of the research who admit the appropriation of the mobile device, the cell phone, to obtain formal and informal literacies, in different social practices, for the production of sociability with affinity groups and belongings linked to the ludic and entertainment. In addition, these young people use cell phones to acquire learning in relation to the world interconnected by digital culture, referring them to the insertion in social benefit programs, in public policies and in resolving issues related to the exercise of citizenship. However, these young people complain about the adverse use of cell phones to spread fake news, acts of violence and destruction. Still, they denounce the scarcity of infrastructure to support the online connection capable of enhancing school pedagogical mediation to reach knowledge related to the various fields. Another demand brought by these research subjects refers to the role of the school in the development of critical and ethical awareness.